Anticancer Effect and Mechanism of Hydroxygenkwanin in Oral Squamous Cell Carcinoma - Huang, Yi-Chao; Lee, Po-Chuan; Wang, Jane Jen; Hsu, Yi-Chiung (Frontiers in Oncology, 2019)
The incidence and mortality of oral squamous cell carcinoma (OSCC) are high, and the number of oral cancers had risen in the world. However, chemotherapy drugs have numerous side effects. There is an urgent requirement to develop a novel drug that can be used to treat oral cancer. Hydroxygenkwanin (HGK) is a nature flavonoid extracted from Daphne genkwa Sieb. et Zucc. (Thymelaeaceae). Previous studies had demonstrated that HGK exhibits anticancer effect, but the effect is still unclear in oral cancer. HGK inhibited cell growth dose-dependently in SAS and OCEM1 cells. The functional enrichment analysis showed the significant pathway in cellular movement, cell cycle and cellular growth and proliferation. We further demonstrated the HGK induced the cell cycle arrest by flow cytometry and inhibited colony formation ability and cell movement. The western blot showed that HGK induced cell cycle arrest through p21 activation and caused intrinsic cell apoptosis pathway. HGK inhibited the cell invasion and migration through down-regulation vimentin. HGK might be an effective natural product for oral cancer therapy.